Comparison of Mephentermine, Ephedrine and Phenylephrine for Treating Hypotension after Spinal Anesthesia in Caesarean Section - Shakya, Shailendra; Shakya, Anuka; Nepal, Ashmita; Khatik, Chandra (Journal of Nepalgunj Medical College, 2025)
Introduction: Hypotension is a common complication during spinal anesthesia in the caesarean section, often requiring vasopressors for correction. This study compares the effects of Mephentermine, Ephedrine, and Phenylephrine in maintaining arterial pressure.Aims: To evaluate the onset time and efficacy of three vasopressors in reversing hypotension, comparing heart rate responses (bradycardia or tachycardia) and assessing side effects such as nausea, vomiting or shivering. Additionally, neonatal outcomes are assessed using Apgar scores at 1 and 5 minutes to evaluate the impact of each vasopressor.Methods: A prospective, randomized interventional study was conducted among 105 parturients undergoing elective or emergency caesarean section under spinal aesthesia at Nepalgunj Medical College Teaching Hospital. Participants were randomly divided into three equal groups (n=35) to receive intravenous boluses of either Mephentermine 6 mg, Ephedrine 6 mg, or Phenylephrine 80 µg when hypotension occurred. Hemodynamic parameters (Systolic blood pressure, diastolic blood pressure and heart rate), neonatal outcomes and complications were recorded.Results: The Phenylephrine group demonstrated a significantly greater and quicker rise in systolic blood pressure during the first six minutes post-administration (p